SENI TRADISI WAYANG: KEKUATAN DESKRIPSI VERBAL - Alexius Hadni Damarwa (Faculty of Humanities, Jember University, 2015)
Shadow puppet is one of Indonesian traditional arts which has received recognition from UNESCO as a Masterpieces of Oral and Intangible Heritage of Humanity. Shadow puppet is a blend of art, movement, verbal oral, music, and song. The focus of the study in this paper emphasizes on the verbal aspect in the art of shadow pupper tradition called Janturan and tradition song. Both types of verbal aspect are working to build up a certain atmosphere, such as peace, sad, crowded, intimidating, and angry. Therefore, the lingual units are spoken rhythmically and uses the choice of words having the power of the aesthetic in terms of sound and meaning. In addition, the verbal aspect is also to mark the change of time, part of the story, and the transition of gending. All of it is a convention that has become a common understanding between the puppeteers, musicians, and sinden ‘singer’. Spectators classified pandhemen or militant fans already understand the conventions and storyline.Keywords: description, janturan, tradition song, puppet